2012
DOI: 10.1007/s10384-012-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of fibronectin in corneal wound healing explored by a physician–scientist

Abstract: For the past 30 years, I have worked as a physician-scientist in both the clinic and laboratory setting at a number of university medical schools. Encountering patients in the clinic for whom treatment was not available led me to the laboratory in an attempt to develop the appropriate treatment for future patients. The main focus of my translational research has been the role of fibronectin in corneal epithelial wound healing and the development of fibronectin eyedrops for the treatment of patients with persis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…Fibronectin, produced by activated stromal fibroblasts, plays an important role in corneal wound healing process 31 . Studies showed that 1 to 2 weeks following epithelial incision, fibronectin provided a provisional matrix to support the migration of the remaining epithelial cells or fibroblasts to cover the area of defect 20 32 . When the wound healing response was complete, the expression of fibronectin began to decrease 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin, produced by activated stromal fibroblasts, plays an important role in corneal wound healing process 31 . Studies showed that 1 to 2 weeks following epithelial incision, fibronectin provided a provisional matrix to support the migration of the remaining epithelial cells or fibroblasts to cover the area of defect 20 32 . When the wound healing response was complete, the expression of fibronectin began to decrease 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Autologous plasma fibronectin eyedrops were thus instituted for the treatment of corneal epithelial disorders at Yamaguchi University Hospital. Our clinical experience with 151 eyes of 146 patients between April 2000 and March 2005 confirmed that fibronectin eyedrops are effective for the treatment of corneal PEDs (72% of 100 eyes responded with complete epithelial resurfacing within 9.5 ± 6.8 days) and simple corneal erosion (91.4% of 35 eyes responded with complete resurfacing within 7.0 ± 6.4 days) (Nishida, 2012). A representative case is shown in Fig.…”
Section: Autologous Fibronectin Eyedropsmentioning
confidence: 53%
“…These factors have included epidermal growth factor (EGF) (Daniele et al, 1979;Ho and Elliott, 1975;Nishida et al, 1990;Schultz et al, 1988;Soong et al, 1989;Watanabe et al, 1987Watanabe et al, , 1988Yu et al, 2010) as well as various other growth factors such as fibroblast growth factor (FGF), hepatocyte growth factor, keratinocyte growth factor, and nerve growth factor (Gospodarowicz et al, 1977;Grant et al, 1992;Lambiase et al, 2000Lambiase et al, , 2012Sotozono et al, 1994;Wilson et al, 1993). In addition, extracellular matrix components such as fibronectin have been shown to facilitate corneal epithelial wound healing (Nishida, 2010b(Nishida, , 2012. A major drawback of many of these biologically active agents has been the induction of unwanted effects on various components of the anterior segment of the eye, such as the induction of corneal neovascularization by EGF.…”
Section: Introductionmentioning
confidence: 99%
“…The use of topical fibronectin has already been reported to improve the corneal healing process (71,72) . The presence of fibronectin was not identified in the CM or the AM.…”
Section: Therapeutic Use Of Gf/cytokines In Ocular Surface Diseasesmentioning
confidence: 99%